Hydroponic systems and water management in aquaponics: A review - Maucieri, Carmelo; Nicoletto, Carlo; Junge, Ranka; Schmautz, Zala; Sambo, Paolo; Borin, Maurizio (Italian Journal of Agronomy, 2017)
Aquaponics (AP), the integrated multi-trophic fish and plants production in quasi-closed recirculating system, is one of the newest sustainable food production systems. The hydroponic component of the AP directly influences water quality (in turn influencing fish growth and health), and water consumption (through evapotranspiration) of the entire system. In order to assess the role of the design and the management of the hydroponic component on the overall performance, and water consumption of the aquaponics, 122 papers published from 1979 to 2017 were reviewed. Although no unequivocal results were found, the nutrient film technique appears in several aspects less efficient than medium-based or floating raft hydroponics. The best system performance in terms of fish and plant growth, and the highest nutrient removal from water was achieved at water flow between 0.8 L min–1 and 8.0 L min–1. Data on water consumption of aquaponics are scarce, and no correlation between the ratio of hydroponic unit surface/fish tank volume and the system water loss was found. However, daily water loss was positively correlated with the hydroponic surface/fish tank volume ratio if the same experimental conditions and/or systems were compared. The plant species grown in hydroponics influenced the daily water loss in aquaponics, whereas no effect was exerted by the water flow (reciprocating flood/drain cycle or constant flow) or type (medium-based, floating or nutrient film technique) of hydroponics.